2012
DOI: 10.2174/138620712798868374
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Research into Bio-Based FDCA-Polyesters by Using Small Scale Parallel Film Reactors

Abstract: High Throughput experimentation has been well established as a tool in early stage catalyst development and catalyst and process scale-up today. One of the more challenging areas of catalytic research is polymer catalysis. The main difference with most non-polymer catalytic conversions is the fact that the product is not a well defined molecule and the catalytic performance cannot be easily expressed only in terms of catalyst activity and selectivity. In polymerization reactions, polymer chains are formed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 4 publications
3
76
0
1
Order By: Relevance
“…11,12,14,25,30,31,40,110 In 2012 Gruter et al 109 published an in-depth systematic study about several parameters affecting this 2-(or 3-) stage polymerisation approach, namely starting monomers, temperature, and especially the catalysts used. These parameters were assessed in terms of colour, yields and molecular weight.…”
Section: Poly(ethylene 25-furandicarboxylate)mentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,14,25,30,31,40,110 In 2012 Gruter et al 109 published an in-depth systematic study about several parameters affecting this 2-(or 3-) stage polymerisation approach, namely starting monomers, temperature, and especially the catalysts used. These parameters were assessed in terms of colour, yields and molecular weight.…”
Section: Poly(ethylene 25-furandicarboxylate)mentioning
confidence: 99%
“…In the same vein, increasing the polymerisation temperature up to 260-280 o C, as used in PET counterpart, resulted in yellowish coloured products (a really huge problem in certain applications like for example in packaging) and lower yields. An extensive catalyst screening was carried out in this same study, 109 in which 45 different metal catalysts were compared. Results revealed that the highest yields were obtained for dibutyltin(IV) oxide and titanium(IV) isopropoxide, although when the former was used a more coloured product was obtained.…”
Section: Poly(ethylene 25-furandicarboxylate)mentioning
confidence: 99%
“…Such times are too high and can cause coloration to the final polyester. With the method proposed in the current study, the coloration is limited, as was mentioned in previous studies, and is temperature dependent …”
Section: Resultsmentioning
confidence: 92%
“…The coloration of the FDCA/2,5‐dimethylfuran dicarboxylate (DMFD)‐based materials can have three origins, namely, sugar‐based impurities in the monomer, side reactions (e.g., decarboxylation) taking place during the polymer synthesis, or the presence of various additives . It was also found that catalysts such as manganese, cobalt, and germanium result in a strongly colored PEF product . Furthermore, as was reported by de Jong et al, there is a clear relationship between the amount of FDCA and the amount of color formed.…”
Section: Introductionmentioning
confidence: 78%
“…A specific target is poly(ethylene terephthalate) (PET), which is a fossil-based polyester with a market volume of 50 million tons per year [93]. Several groups have investigated furan analogs to PET using the 2,5-FDCA furan derivative [89,91,92,[94][95][96][97]. There are several synthetic routes to polyesters based on FDCA, including solution polycondensation, polytransesterification, and solid-state postcondensation [91,92].…”
Section: Polyestersmentioning
confidence: 99%